Delayed embolization of ductal occluder device into the aorta with near‐complete obstruction of the aorta and critical cardiac decompensation. Issue 3 (23rd January 2020) - Jaswal, Vivek; Singh Thingnam, Shyam Kumar; Prasad Gourav, Krishna; Halder, Vikram
Abstract: Delayed embolization of ductal occluder device into the aorta after transcatheter closure of a patent ductus arteriosus (PDA) with almost complete obstruction of the aorta is extremely rare. Our patient had delayed migration of a ductal occluder device into the descending thoracic aorta (DTA) 6 months after its deployment. Because of critical biventricular dysfunction, urgent surgical removal of the device from the descending aorta was done via left posterolateral thoracotomy without using cardiopulmonary bypass. PDA was not closed because of doubt about the reversibility of pulmonary artery hypertension and severe right ventricular dysfunction so that it can act as an outlet to the decompensated right ventricle. The patient made an uneventful recovery. The patient was started on pulmonary vasodilators and is planned for right heart catheterization study after 2 months to check for the operability of PDA.